A distributed bragg mirror structure and a VCSEL device

By designing a distributed Bragg reflector structure, the problems of reflection bandwidth, absorption loss, oxidation compatibility, and spot control in VCSEL devices with traditional N-type DBR structures were solved, achieving wide bandwidth, low absorption, and spot compression, thus improving device performance and consistency.

CN123034210APending Publication Date: 2026-11-03YANGZHOU CHANGELIGHT +1
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611216655.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-08-12
Publication Date
2026-11-03

AI Technical Summary

Technical Problem

Traditional N-type DBR structures in VCSEL devices suffer from contradictions between reflection bandwidth and absorption loss, oxidation compatibility issues, and limited spot control capabilities, making it difficult to simultaneously meet the requirements of wide bandwidth, low absorption, and high spot control.

Method used

A distributed Bragg reflector structure is adopted. Multiple clusters are set in the N-type DBR layer. Each cluster consists of alternating stacks of high-refractive-index AlxGa1-xAs layers and low-refractive-index AlyGa1-yAs layers. The x value gradually increases and the y value gradually decreases. Furthermore, the Al composition of the uppermost cluster is lower than that of the oxide confinement layer, thereby achieving a continuous and smooth decay of the refractive index difference and avoiding the phenomenon of oxidation stealing oxygen.

Benefits of technology

It achieves a balance between wide reflection bandwidth and low absorption loss, improves the slope efficiency and output power of the device, ensures spot size compression and beam quality, improves device yield and consistency, and is compatible with existing oxidation processes.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN123034210A_ABST
    Figure CN123034210A_ABST
Patent Text Reader

Abstract

This invention discloses a distributed Bragg reflector structure and a VCSEL device. The distributed Bragg reflector structure is an N-type DBR layer in a semiconductor device, located below the active region of the semiconductor device, and includes multiple independent clusters from bottom to top. Each cluster consists of multiple pairs of high-refractive-index Al atoms. x Ga 1‑x As layer and low refractive index Al y Ga 1‑y The As layers are stacked alternately, where 0≤x≤0.5, 0.8≤y≤1, and the x value gradually increases from the bottom cluster to the top cluster, or shows a monotonically non-decreasing trend, and the x value of the top cluster is greater than that of the bottom cluster; the y value gradually decreases from the bottom cluster to the top cluster, or shows a monotonically non-increasing trend, and the y value of the top cluster is less than that of the bottom cluster. This application solves the problems of bandwidth, absorption, oxidation compatibility and spot control requirements through the above structure.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of semiconductor device technology, and specifically relates to a distributed Bragg reflector structure and a VCSEL device. Background Technology

[0002] Vertical-cavity surface-emitting lasers (VCSELs) have become key light sources in fields such as optical communication, 3D sensing, and lidar due to their advantages such as low threshold current, circular output spot, and ease of two-dimensional integration. The core structure of a VCSEL consists of two Bragg mirrors (DBRs) distributed at the top and bottom and an active region in the middle. The performance of the DBRs directly affects the threshold characteristics, output efficiency, and beam quality of the device.

[0003] Traditional N-type DBRs typically employ a fixed-composition AlGaAs material pair (e.g., Al...). 0.12 Ga 0.88 As / Al 0.9 Ga 0.1 As) are stacked alternately. However, this uniform design has the following inherent contradiction: 1. The contradiction between reflection bandwidth and absorption loss: To achieve a wide reflection bandwidth, materials with a large refractive index difference (such as AlAs / GaAs) are required. However, GaAs exhibits significant free carrier absorption in the long wavelength range, especially under high N-type doping, resulting in severe absorption loss and affecting laser output efficiency.

[0004] 2. Oxidation process compatibility issues: Traditional DBR contains a high-Al component layer (such as Al...). 0.9 Ga 0.1 In the process of wet oxidation to prepare the oxide confinement layer (including AlAs and AlAs), these high-Al layers will "compete" for oxygen atoms with the oxide confinement layer (which is also a high-Al component), that is, an "oxygen grabbing" phenomenon occurs, which leads to uncontrolled oxidation rate and uneven oxidation depth, seriously affecting device yield and consistency.

[0005] 3. Spot control requirements: In applications such as high-density arrays or single-mode fiber coupling, small spot output is required, but traditional DBR designs have limited ability to control the spot size.

[0006] Therefore, there is an urgent need for an innovative N-type DBR structure design that can simultaneously address multiple requirements such as bandwidth, absorption, oxidation compatibility, and spot control. Summary of the Invention

[0007] The purpose of this invention is to provide a distributed Bragg reflector structure and VCSEL device to solve problems such as bandwidth, absorption, oxidation compatibility and spot control requirements.

[0008] To achieve the above objectives, this application provides a distributed Bragg reflector structure, which is an N-type DBR layer in a semiconductor device, located below the active region of the semiconductor device. Its characteristic is that it comprises multiple independent clusters from bottom to top, each cluster consisting of multiple pairs of high-refractive-index Al atoms. x Ga 1-x As layer and low refractive index Al y Ga 1-y The As layers are stacked alternately, where 0≤x≤0.5, 0.8≤y≤1, and the x value is set to gradually increase from the bottom cluster to the top cluster, or shows a monotonically non-decreasing trend, and the x value of the top cluster is greater than the x value of the bottom cluster; the y value is set to gradually decrease from the bottom cluster to the top cluster, or shows a monotonically non-increasing trend, and the y value of the top cluster is less than the y value of the bottom cluster.

[0009] Furthermore, the uppermost cluster is close to the active region, and the uppermost Al y Ga 1-y The y-value range in the As layer is 0.85 ≤ y ≤ 0.94, and the doping amount is 3 × 10⁻⁶. 17 cm -3 ~6×10 17 cm -3 This includes endpoint values.

[0010] Furthermore, each group has multiple pairs of AI x Ga 1-x As layer and Al y Ga 1-y In the As layer, x values ​​can be set to be the same or gradually changed, and y values ​​can also be set to be the same or gradually changed.

[0011] Furthermore, the bottom layer of each cluster is a high-refractive-index Al layer. x Ga 1-x The As layer, with the top layer being low-refractive-index Al. y Ga 1-y As layer.

[0012] Furthermore, the N-type DBR layer includes a first group, a second group, and a third group from bottom to top. The x-values ​​and y-values ​​in each group are the same. In the first group, x=0 and y=1; in the second group, x=0 and y=0.9; and in the third group, x=0.2 and y=0.8.

[0013] Furthermore, the first group consists of 7 pairs of Al x Ga 1-x As layer and Al y Ga 1-y It consists of an As layer with a doping concentration of 2×10⁻⁶. 18 cm -3 The second group consists of 24 pairs of Alx Ga 1-x As layer and Al y Ga 1-y The layer consists of an As layer with a doping concentration of 1×10⁻⁶. 18 cm -3 The third group consists of 7 pairs of Al x Ga 1-x As layer and Al y Ga 1-y It consists of an As layer with a doping concentration of 5 × 10⁻⁶. 17 cm -3 .

[0014] Furthermore, the N-type DBR layer comprises a first group, a second group, a third group, and a fourth group from bottom to top. The first group, the third group, and the fourth group have the same x value and the same y value. In the first group, x=0 and y=1. In the second group, x gradually changes from 0 to 0.15 and y gradually changes from 1 to 0.9. In the third group, x=0.15 and y=0.9. In the fourth group, x=0.2 and y=0.8.

[0015] Furthermore, the first group consists of 5 pairs of Al x Ga 1-x As layer and Al y Ga 1-y It consists of an As layer with a doping concentration of 2×10⁻⁶. 18 cm -3 The second group consists of 5 pairs of Al x Ga 1-x As layer and Al y Ga 1-y It consists of an As layer with a doping concentration of 1.5 × 10⁻⁶. 18 cm -3 The third group consists of 30 pairs of Al x Ga 1-x As layer and Al y Ga 1-y It consists of an As layer with a doping concentration of 5 × 10⁻⁶. 17 cm -3 The fourth group consists of 6 pairs of Al x Ga 1-x As layer and Al y Ga 1-y It consists of an As layer with a doping concentration of 5 × 10⁻⁶. 17 cm -3 .

[0016] Furthermore, the high refractive index Al x Ga 1-x As layer and low refractive index Al y Ga1-y The thickness of the As layer is 20nm-120nm, including the endpoint values.

[0017] This application also provides a VCSEL device, comprising a substrate, an N-type DBR layer as described in any one of claims 1-9, an active region, an oxide confinement layer, and a P-type DBR layer, wherein the oxide confinement layer is Al. x1 Ga 1-x1 As layer, where x1 ≥ 0.98.

[0018] Furthermore, a lower spacer layer is provided between the N-type DBR layer and the active region, and an upper spacer layer is provided between the oxide confinement layer and the active region.

[0019] After adopting the above solution, the beneficial effects of the present invention are as follows: 1. Achieving both wide reflection bandwidth and low absorption loss: This application features an N-type DBR layer with multiple clusters, each cluster consisting of multiple pairs of high-refractive-index Al atoms. x Ga 1-x As layer and low refractive index Al y Ga 1-y The Al layers are alternately stacked, with the x-values ​​gradually increasing from the bottom to the top, or exhibiting a monotonically non-decreasing trend, and the x-value of the top cluster being greater than that of the bottom cluster; the y-values ​​gradually decrease from the bottom to the top cluster, or exhibit a monotonically non-increasing trend, and the y-value of the top cluster being less than that of the bottom cluster. Since the Al content is inversely proportional to the refractive index, the refractive index difference of the bottom clusters (i.e., Al...) x Ga 1-x As layer and Al y Ga 1-y The refractive index difference of the As layer is greater than that of the top cluster. The large refractive index difference of the bottom cluster ensures a wide reflection bandwidth, effectively reflecting light rays emitted from the active region at various angles and reducing the threshold current. Meanwhile, the top cluster, with its small refractive index difference and low absorption (doped at 3 × 10⁻⁶),... 17 cm -3 ~6×10 17 cm -3 The grouping of these components minimizes the absorption of free carriers during the output laser emission process, improving the device's slope efficiency and output power, and achieving an ideal balance between high reflectivity and low absorption.

[0020] 2. Eliminate the "oxygen-stealing" phenomenon of oxidation: In traditional N-type DBRs, the top high-Al layer (i.e., low-refractive-index Al) 0.92 Ga 0.08 The As layer competes with the oxide confinement layer above the active region for oxygen atoms, a phenomenon known as "oxygen grabbing." The Al group at the top of this application... y Ga1-y The As layer uses a low Al content material, with an Al content of only 0.85. Its affinity for oxygen is much lower than that of a true oxide confinement layer (the Al content of an oxide confinement layer is usually ≥0.98). Therefore, during the wet oxidation process, oxygen atoms preferentially and only react with the oxide confinement layer. The top clusters of the N-type DBR layer basically do not participate in the oxidation reaction, which fundamentally solves the process control problem caused by "oxygen grabbing". It achieves precise and uniform control of oxidation depth and contour, and greatly improves device yield and consistency.

[0021] 3. Achieving Beam Spot Compression and Mode Control: The large refractive index difference in the bottom cluster exerts a stronger constraint on the optical field, suppressing its lateral expansion at the bottom; while the small refractive index difference in the top cluster provides weaker constraint. This asymmetric optical field constraint design alters the mode distribution within the resonant cavity, increases the diffraction loss of higher-order transverse modes, and facilitates the selective excitation of the fundamental transverse mode, thereby effectively compressing the output beam spot size and achieving superior far-field divergence angle and beam quality (M). 2 With a factor closer to 1, it is particularly suitable for applications requiring small spot size and high beam quality.

[0022] 4. Comprehensive performance improvement and process compatibility: The above design improves the optical and electrical performance of the device while being perfectly compatible with existing oxidation processes. It does not require any additional photolithography or etching steps and can be achieved simply by controlling the composition during epitaxial growth. It has extremely high practical value and industrialization prospects. Attached Figure Description

[0023] Figure 1 This is a structural diagram of the VCSEL device of the present invention; Figure 2 This is a structural diagram of the N-type DBR layer in Embodiment 1 of the present invention; Figure 3 This is a structural diagram of the N-type DBR layer in Embodiment 2 of the present invention.

[0024] Label Explanation: 1. Substrate; 2. GaAs buffer layer; 3. N-type DBR layer; 4. Lower spacer layer; 5. Active region; 6. Upper spacer layer; 7. Oxide confinement layer; 8. P-type DBR layer; 9. P-type contact layer. Detailed Implementation

[0025] The technical solutions of the embodiments of this application will be clearly and completely described below with reference to the accompanying drawings. Obviously, the described embodiments are only some embodiments of this application, and not all embodiments. Based on the embodiments of this application, all other embodiments obtained by those of ordinary skill in the art without creative effort are within the scope of protection of this application, and the range values ​​mentioned in this application all include endpoint values.

[0026] Key references Figures 1-3 This invention provides a distributed Bragg reflector structure, which is an N-type DBR layer 3 in a semiconductor device, located below the active region of the semiconductor device, with an oxide confinement layer above the active region. The N-type DBR layer 3 includes multiple independent clusters from bottom to top, and each cluster consists of multiple pairs of high-refractive-index Al atoms. x Ga 1-x As layer and low refractive index Al y Ga 1-y The As layers are alternately stacked, where 0 ≤ x ≤ 0.5, 0.8 ≤ y ≤ 1, and the x-value gradually increases from the bottom cluster to the top cluster, or exhibits a monotonically non-decreasing trend. The x-value of the top cluster is greater than that of the bottom cluster; that is, the x-value can gradually increase from the bottom cluster to the top cluster, or the x-value of the lower clusters can remain constant while increasing in the top clusters. The y-value gradually decreases from the bottom cluster to the top cluster, or exhibits a monotonically non-increasing trend. The y-value of the top cluster is less than that of the bottom cluster. Similarly, the y-value can gradually decrease from the bottom cluster to the top cluster, or the y-value of the lower clusters can remain constant while decreasing in the top clusters. The top cluster is close to the active region 5, and the top Al... y Ga 1-y The y-value range in the As layer is 0.85 ≤ y ≤ 0.94, and the doping concentration is 3 × 10⁻⁶. 17 cm -3 ~6×10 17 cm -3 The refractive index of a material is inversely proportional to the Al content; therefore, the refractive index difference of the bottom clusters (i.e., Al content) x Ga 1-x As layer and Al y Ga 1-y The refractive index difference of the As layer is greater than that of the top cluster. The large refractive index difference of the bottom cluster ensures a wide reflection bandwidth, effectively reflecting light rays emitted from the active region 5 at various angles and reducing the threshold current. Meanwhile, the small refractive index difference and low absorption of the top cluster minimize free carrier absorption during the output laser emission process, improving the device's slope efficiency and output power, achieving an ideal balance between high reflectivity and low absorption. The low-absorption cluster at the top is set with a low doping concentration of 3 × 10⁻⁶. 17 cm -3 ~6×10 17 cm -3 If the doping amount is less than 3×10 17 cm -3This will lead to a significant decrease in the conductivity of the DBR, an increase in the device's series resistance, and increased heat generation; if the doping concentration is higher than 6×10 17 cm -3 This will lead to an increase in free carrier concentration, a significant rebound in light absorption loss, and the loss of low absorption effect.

[0027] Furthermore, the Al composition of both the high and low refractive index layers in this application is varied, which differs from a single-layer composition variation scheme (i.e., only varying the Al composition of the high or low refractive index layer). This allows for continuous and smooth attenuation of the refractive index difference, uniform distribution of lattice stress, and smoothing of the band barrier to reduce internal resistance. Simultaneously, layered suppression of free carrier absorption and precise control of the low Al composition of the top layer solve the oxidation and oxygen grabbing problem. It can also smoothly regulate the intracavity optical field distribution, compress the beam spot, and stabilize the fundamental transverse mode. This achieves synergistic optimization in terms of reflection bandwidth, optical loss, process compatibility, beam quality, and device reliability, and its overall performance is superior to a single-layer composition variation structure.

[0028] The Al content of the oxidation confinement layer 7 is typically ≥0.98, while the high Al layer at the top of a conventional N-type DBR is generally Al. 0.92 Ga 0.08 The As layer, with its high Al content, competes with the oxide confinement layer for oxygen atoms, resulting in an "oxygen grabbing" phenomenon. Therefore, this application sets the uppermost Al group... y Ga 1-y The As layer uses a low-Al content material (Al content is only 0.85), which has a much lower affinity for oxygen than the oxidation confinement layer. During the wet oxidation process, oxygen atoms preferentially and only react with the oxidation confinement layer. The top clusters of the N-type DBR layer 3 basically do not participate in the oxidation reaction, which fundamentally solves the process control problem caused by "oxygen grabbing". It achieves precise and uniform control of oxidation depth and contour, and greatly improves device yield and consistency.

[0029] Optional, multiple pairs of AI in each group x Ga 1-x As layer and Al y Ga 1-y In the As layer, the x-value is set to be the same or gradually changed, and the y-value is set to be the same or gradually changed. The gradual change is set to linearly increase or decrease the component within the thickness range. The component gradual change can avoid the large potential barrier step difference between high and low Al components, which would lead to an increase in internal resistance and reduce the internal resistance.

[0030] Specifically, the bottom layer of each cluster is high-refractive-index Al. x Ga 1-x The As layer, with the top layer being low-refractive-index Al. y Ga 1-y As layer, with Al x Ga 1-x As layer / Aly Ga 1-y The As layers are stacked in a cyclical pattern, i.e., in a high-refractive-index / low-refractive-index cycle, with each layer having an optical thickness of λ / 4. The advantages of this arrangement are: the high-refractive-index layer grown directly at the bottom layer can smoothly connect with the underlying GaAs lattice, doping type, and band structure; the substrate and buffer layer below are also made of GaAs (a high-refractive-index material system); growing the high-refractive-index layer first avoids abrupt changes in the material system, resulting in fewer interface defects and lower series resistance. If the low-refractive-index layer (Al) is grown first in reverse order... y Ga 1-y The lattice mismatch at the GaAs-high AlAs interface (As layer) increases sharply, generating numerous interface states and nonradiative recombination centers, leading to increased device leakage and heat generation. Furthermore, this stacking design optimizes the interface stress near the top of the active region. Each cluster's top layer terminates in a low-refractive-index layer, directly connecting to the lower spacer layer. This allows for a smooth transition in Al composition with the lower spacer layer, eliminating high-Al abrupt transition layers and significantly alleviating epitaxial stress, protecting the active region's quantum well. If the stack were inverted, the top cluster's high-refractive-index termination would cause a significant increase in charge carriers, negating the low-absorption design advantages. In addition, this stacking design smoothly transitions energy bands and refractive indices, reducing periodic barrier spikes and device internal resistance, satisfying the reflection phase abrupt transition condition, and ensuring high reflectivity across the entire wavelength range.

[0031] Optionally, the high refractive index Al x Ga 1-x As layer and low refractive index Al y Ga 1-y The thickness of the As layer is 20nm-120nm, including the endpoint values, which conforms to the total reflection thickness.

[0032] like Figure 2 As shown, in one embodiment, the N-type DBR layer includes a first cluster, a second cluster, and a third cluster from bottom to top. Each cluster has the same x and y values: x=0, y=1 in the first cluster, x=0, y=0.9 in the second cluster, and x=0.2, y=0.8 in the third cluster. The first cluster consists of 7 pairs of Al... x Ga 1-x As layer and Al y Ga 1-y It consists of an As layer with a doping concentration of 2×10⁻⁶. 18 cm -3 The second group consists of 24 pairs of Al x Ga 1-x As layer and Al y Ga 1-y The layer consists of an As layer with a doping concentration of 1×10⁻⁶. 18 cm -3 The third group consists of 7 pairs of Al x Ga1-x As layer and Al y Ga 1-y It consists of an As layer with a doping concentration of 5 × 10⁻⁶. 17 cm -3 .

[0033] like Figure 3 As shown, in another embodiment, the N-type DBR layer comprises, from bottom to top, a first group, a second group, a third group, and a fourth group. The first, third, and fourth groups have the same x and y values. Specifically, in the first group, x=0 and y=1; in the second group, x gradually changes from 0 to 0.15 and y gradually changes from 1 to 0.9; in the third group, x=0.15 and y=0.9; and in the fourth group, x=0.2 and y=0.8. The first group consists of 5 pairs of Al... x Ga 1-x As layer and Al y Ga 1-y It consists of an As layer with a doping concentration of 2×10⁻⁶. 18 cm -3 The second group consists of 5 pairs of Al x Ga 1-x As layer and Al y Ga 1-y It consists of an As layer with a doping concentration of 1.5 × 10⁻⁶. 18 cm -3 The third group consists of 30 pairs of Al x Ga 1-x As layer and Al y Ga 1-y It consists of an As layer with a doping concentration of 5 × 10⁻⁶. 17 cm -3 The fourth group consists of 6 pairs of Al x Ga 1-x As layer and Al y Ga 1-y It consists of an As layer with a doping concentration of 5 × 10⁻⁶. 17 cm -3 .

[0034] like Figure 1 As shown, this application also provides a VCSEL device, including a substrate 1, a GaAs buffer layer 2, the aforementioned N-type DBR layer 3, a lower spacer layer 4, an active region 5, an upper spacer layer 6, an oxide confinement layer 7, a P-type DBR layer 8, and a P-type contact layer 9. The substrate 1 may be a GaAs substrate, and the oxide confinement layer 7 may be an Al substrate. x1 Ga 1-x1 As layer, where x1 ≥ 0.98. The oxidation confinement layer 7 is typically prepared by wet oxidation, and the oxidation confinement layer 7 is typically Al. 0.98 Ga0.02 In the As layer, since the Al composition of the uppermost group of the N-type DBR layer is 0.85, its affinity for oxygen is much lower than that of Al. 0.98 Ga 0.02 As layer, oxygen atoms preferentially react with oxidation confinement layer 7 during oxidation, and the top clusters of N-type DBR layer 3 are hardly oxidized, achieving precise control of oxidation depth and reducing stress between N-type DBR layer 3 and active region 5.

[0035] Specifically, the active region consists of multiple pairs of InGaAs / GaAsP.

[0036] The following specific examples further illustrate this point.

[0037] Example 1: For a VCSEL device in the 940nm band, a three-group N-type DBR layer is set. The specific VCSEL device includes the following structure from bottom to top: Substrate: N-type GaAs substrate with a doping concentration of 2×10⁻⁶. 18 cm -3 .

[0038] N-type DBR layer: such as Figure 2 As shown, high refractive index Al x Ga 1-x As layer and low refractive index Al y Ga 1-y The As layer has a total of 38 pairs, which are divided into 3 groups from bottom to top, as follows: First cluster: Located at the very bottom, high refractive index Al x Ga 1-x As layer and low refractive index Al y Ga 1-y The As layer has 7 pairs, and all pairs have the same x-value and the same y-value. Specifically: High refractive index Al x Ga 1-x The Al component in the As layer is x=0, which is a GaAs layer. The thickness is designed to be 65.3nm based on the 940nm wavelength. The refractive index is 3.6 and the optical thickness is λ / 4. Low refractive index Al y Ga 1-y The As layer has an Al composition y=1, forming an AlAs layer. Its thickness is designed to be 79.7nm based on a 940nm wavelength, with a refractive index of 2.95 and an optical thickness of λ / 4. The doping concentration is: n = 2 × 10 18 cm -3 ; Function: Provides the widest reflection bandwidth (>100nm), ensuring efficient reflection of light from various angles emitted from the active region.

[0039] Second group: Located in the central part, high refractive index Al x Ga 1-x As layer and low refractive index Al y Ga 1-y The As layer has 24 pairs, and all pairs have the same x-value and the same y-value. Among them: High refractive index Al x Ga 1-x The Al component in the As layer is x=0, which is a GaAs layer. The thickness is designed to be 65.3nm based on the 940nm wavelength. The refractive index is 3.6 and the optical thickness is λ / 4. Low refractive index Al y Ga 1-y The Al component in the As layer has an y=0.9 value and is Al. 0.9 Ga 0.1 The As layer has a thickness of 78.5 nm designed according to the 940 nm wavelength, a refractive index of 3, and an optical thickness of λ / 4. The doping concentration is: n = 1 × 10 18 cm -3 (The doping level is slightly lower than that of the bottom cluster to reduce absorption); Function: To serve as the primary reflection area.

[0040] Third group: Located at the very top, high refractive index Al x Ga 1-x As layer and low refractive index Al y Ga 1-y The As layer has 7 pairs, and all pairs have the same x-value and the same y-value. Specifically: High refractive index Al x Ga 1-x The Al component in the As layer has an Al content of x=0.2, which is Al. 0.2 Ga 0.8 The As layer has a thickness of 67.5 nm designed for a 940 nm wavelength, a refractive index of 3.48, and an optical thickness of λ / 4. Low refractive index Al y Ga 1-y The Al component in the As layer has an y=0.85, which is Al 0.85 Ga 0.15 The As layer has a thickness of 74.6 nm designed for a 940 nm wavelength, a refractive index of 3.15, and an optical thickness of λ / 4. The doping concentration is: n = 5 × 10 17 cm -3 (For low doping to minimize free carrier absorption); Function: To minimize the absorption of the output laser, reduce the stress of oxidation on the active region, and form a good interface match with the upper P-type DBR layer and oxide confinement layer.

[0041] The structure above the N-type DBR layer 3, from bottom to top, consists of: lower spacer layer 4, active region 5 (composed of multiple pairs of InGaAs / GaAsP), upper spacer layer 6, and oxide confinement layer 7 (composed of high-Al content Al). 0.98 Ga 0.02 The structure consists of an As layer, a P-type DBR layer 8 (using a conventional design), and a P-type contact layer 9. The oxidation confinement layer 7 is prepared using a wet oxidation process. Because the Al content of the third group at the top is the highest at 0.85, its affinity for oxygen is much lower than that of Al. 0.98 Ga 0.02 As the oxidation confinement layer 7, oxygen atoms preferentially react with the oxidation confinement layer 7 during the oxidation process, and the top of the N-type DBR layer 3 is hardly oxidized, thus achieving precise control of the oxidation depth and reducing the stress between the N-type DBR layer 3 and the active region 5.

[0042] Tests showed that the output spot diameter of the above structure was reduced by about 15% compared with the traditional structure, the far-field divergence angle was reduced by 20%, and the fundamental transverse mode stability was significantly improved.

[0043] Example 2: For VCSEL devices in the 850nm band, such as Figure 3 As shown, the difference from Example 1 is the provision of a four-group N-type DBR layer, and the high refractive index Al in it... x Ga 1-x As layer and low refractive index Al y Ga 1-y The As layer has a total of 46 pairs, which are divided into 4 groups from bottom to top, as follows: First cluster: Located at the very bottom, high refractive index Al x Ga 1-x As layer and low refractive index Al y Ga 1-y The As layer has 5 pairs, and all pairs have the same x-value and the same y-value. Specifically: High refractive index Al x Ga 1-x The Al component in the As layer is x=0, which is a GaAs layer. The thickness is designed to be 59nm based on the 850nm wavelength. The refractive index is 3.6 and the optical thickness is λ / 4. Low refractive index Al y Ga 1-y The As layer has an Al composition y=1, forming an AlAs layer. The thickness is designed to be 72nm based on an 850nm wavelength, with a refractive index of 2.95 and an optical thickness of λ / 4. The doping concentration is: n = 2 × 1018 cm -3 ; Function: Provides the widest reflection bandwidth, ensuring efficient reflection of light from various angles emitted from the active region.

[0044] The second group: located in the middle and above the first group, high-refractive-index Al. x Ga 1-x As layer and low refractive index Al y Ga 1-y The As layer has 5 pairs, with the x-values ​​gradually increasing from bottom to top and the y-values ​​gradually decreasing from bottom to top. Specifically: High refractive index Al x Ga 1-x The Al composition x in the As layer gradually increases from 0 to 0.15 from bottom to top. The thickness of each layer is designed to be 60.7 nm based on the 850 nm wavelength, with an optical thickness of λ / 4 and a refractive index of 3.5. Low refractive index Al y Ga 1-y In the As layer, the Al composition y gradually decreases from 1 to 0.9 from bottom to top. The thickness of each layer is designed according to the 850nm wavelength, with a thickness of 70.8nm, an optical thickness of λ / 4, and a refractive index of 3. The doping concentration is: n = 1.5 × 10⁻⁶ 18 cm -3 ; Function: To serve as a transition zone.

[0045] The third group: located in the middle and above the second group, with high refractive index Al. x Ga 1-x As layer and low refractive index Al y Ga 1-y The As layer has 30 pairs, and all pairs have the same x-value and the same y-value. Among them: High refractive index Al x Ga 1-x The Al component in the As layer has an Al content of x=0.15, which is Al. 0.15 Ga 0.85 The As layer has a thickness of 60.7 nm per layer, designed for an 850 nm wavelength, with an optical thickness of λ / 4 and a refractive index of 3.5. Low refractive index Al y Ga 1-y The Al component in the As layer has an y=0.9 value and is Al. 0.9 Ga 0.1 The As layer has a thickness of 70.8 mm per layer, designed for an 850 nm wavelength, with an optical thickness of λ / 4 and a refractive index of 3. The doping concentration is: n = 5 × 10 17cm -3 (For low doping to minimize free carrier absorption); Function: To serve as the primary reflection area.

[0046] Fourth group: Located at the very top, high refractive index Al x Ga 1-x As layer and low refractive index Al y Ga 1-y The As layer has 6 pairs, and all pairs have the same x and y values. Specifically: High refractive index Al x Ga 1-x The Al component in the As layer has an Al content of x=0.2, which is Al. 0.2 Ga 0.8 The As layer has a thickness of 61.1 nm per layer, designed for an 850 nm wavelength, with an optical thickness of λ / 4 and a refractive index of 3.48. Low refractive index Al y Ga 1-y The Al component in the As layer has an y=0.85, which is Al 0.85 Ga 0.15 The As layer has a thickness of 67.5 nm per layer, designed for an 850 nm wavelength, with an optical thickness of λ / 4 and a refractive index of 3.15. The doping concentration is: n = 5 × 10 17 cm -3 (For low doping to minimize free carrier absorption); Function: To minimize the absorption of the output laser, reduce the stress of oxidation on the active region, and form a good interface match with the upper P-type DBR layer and oxide confinement layer.

[0047] Since the Al content of the top fourth group is the highest at 0.85, the "oxygen-stealing" problem is solved in the same way as in Example 1. According to the test, the above structure of this embodiment has a reflectivity of >99.9% at 850nm, a reflection bandwidth of >90nm, the absorption loss of the top of the N-type DBR is reduced by about 60% compared with the traditional uniform structure, the oxidation process window is significantly expanded, the oxidation depth uniformity is improved by more than 30%, the output spot diameter is reduced by about 15% compared with the traditional structure, the far-field divergence angle is reduced by 20%, and the fundamental transverse mode stability is significantly improved.

[0048] It is important to note that the thicknesses shown in the accompanying drawings are merely examples and do not represent actual thicknesses. Furthermore, the actual proportions between them are not as shown in the drawings and are for reference only.

[0049] The various embodiments in this specification are described in a progressive manner, with each embodiment focusing on the differences from other embodiments. The same or similar parts between the various embodiments can be referred to each other.

[0050] The above description of the disclosed embodiments enables those skilled in the art to make or use this application. Various modifications to these embodiments will be readily apparent to those skilled in the art, and the general principles defined herein may be implemented in other embodiments without departing from the spirit or scope of this application. Therefore, this application is not to be limited to the embodiments shown herein, but is to be accorded the widest scope consistent with the principles and novel features disclosed herein.

Claims

1. A distributed Bragg reflector structure, which is an N-type DBR layer in a semiconductor device, located below the active region of the semiconductor device, characterized in that: It includes multiple independent clusters from bottom to top, each cluster consisting of multiple pairs of high-refractive-index Al atoms. x Ga 1-x As layer and low refractive index Al y Ga 1-y The As layers are stacked alternately, where 0≤x≤0.5, 0.8≤y≤1, and the x value is set to gradually increase from the bottom cluster to the top cluster, or shows a monotonically non-decreasing trend, and the x value of the top cluster is greater than the x value of the bottom cluster; the y value is set to gradually decrease from the bottom cluster to the top cluster, or shows a monotonically non-increasing trend, and the y value of the top cluster is less than the y value of the bottom cluster.

2. The distributed Bragg reflector structure as described in claim 1, characterized in that: The topmost cluster is close to the active zone, and the topmost AI... y Ga 1-y The y-value range in the As layer is 0.85 ≤ y ≤ 0.94, and the doping amount is 3 × 10⁻⁶. 17 cm -3 ~6×10 17 cm -3 This includes endpoint values.

3. The distributed Bragg reflector structure as described in claim 2, characterized in that: Multiple pairs of AI in each group x Ga 1-x As layer and Al y Ga 1-y In the As layer, x values ​​can be set to be the same or gradually changed, and y values ​​can also be set to be the same or gradually changed.

4. The distributed Bragg reflector structure as described in claim 3, characterized in that: The bottom layer of each cluster is high-refractive-index Al. x Ga 1-x The As layer, with the top layer being low-refractive-index Al. y Ga 1-y As layer.

5. A distributed Bragg reflector structure as described in claim 4, characterized in that: The N-type DBR layer includes a first group, a second group, and a third group from bottom to top. Each group has the same x value and the same y value. In the first group, x=0 and y=1; in the second group, x=0 and y=0.9; and in the third group, x=0.2 and y=0.

8.

6. The distributed Bragg reflector structure as described in claim 5, characterized in that: The first group consists of 7 pairs of Al x Ga 1-x As layer and Al y Ga 1-y It consists of an As layer with a doping concentration of 2×10⁻⁶. 18 cm -3 The second group consists of 24 pairs of Al x Ga 1-x As layer and Al y Ga 1-y The layer consists of an As layer with a doping concentration of 1×10⁻⁶. 18 cm -3 The third group consists of 7 pairs of Al x Ga 1-x As layer and Al y Ga 1-y It consists of an As layer with a doping concentration of 5 × 10⁻⁶. 17 cm -3 .

7. The distributed Bragg reflector structure as described in claim 4, characterized in that: The N-type DBR layer comprises a first group, a second group, a third group, and a fourth group from bottom to top. The first, third, and fourth groups have the same x and y values. Specifically, in the first group, x = 0 and y = 1. In the second group, x gradually changes from 0 to 0.15 and y gradually changes from 1 to 0.

9. In the third group, x = 0.15 and y = 0.

9. In the fourth group, x = 0.2 and y = 0.

8.

8. The distributed Bragg reflector structure as described in claim 7, characterized in that: The first group consists of 5 pairs of Al x Ga 1-x As layer and Al y Ga 1-y It consists of an As layer with a doping concentration of 2×10⁻⁶. 18 cm -3 The second group consists of 5 pairs of Al x Ga 1- x As layer and Al y Ga 1-y It consists of an As layer with a doping concentration of 1.5 × 10⁻⁶. 18 cm -3 The third group consists of 30 pairs of Al x Ga 1-x As layer and Al y Ga 1-y It consists of an As layer with a doping concentration of 5 × 10⁻⁶. 17 cm -3 The fourth group consists of 6 pairs of Al x Ga 1-x As layer and Al y Ga 1- y It consists of an As layer with a doping concentration of 5 × 10⁻⁶. 17 cm -3 .

9. A distributed Bragg reflector structure as described in claim 1, characterized in that: The high refractive index Al x Ga 1-x As layer and low refractive index Al y Ga 1-y The thickness of the As layer is 20nm-120nm, including the endpoint values.

10. A VCSEL device, characterized in that: It includes a substrate, an N-type DBR layer as described in any one of claims 1-9, an active region, an oxide confinement layer, and a P-type DBR layer, wherein the oxide confinement layer is Al. x1 Ga 1-x1 As layer, where x1 ≥ 0.

98.

11. A VCSEL device as described in claim 10, characterized in that: A lower spacer layer is provided between the N-type DBR layer and the active region, and an upper spacer layer is provided between the oxidation confinement layer and the active region.